Osteopontin: a novel predictor of survival in patients with systemic light-chain amyloidosis - Kristen, Arnt; Rosenberg, Mark; Lindenmaier, David; Merkle, Corina; Steen, Henning; André, Florian; Schönland, Stefan; Schnabel, Philipp Albert; Schuster, Tibor; Röcken, Christoph; Giannitsis, Evangelos; Katus, Hugo; et al. (Amyloid, 2014)
Background: Troponin-T (cTnT) and NT-proBNP provide prognostic information in light-chain amyloidosis (AL). Thus, these biomarkers are widely used in clinical routine for risk stratification. Recently, plasma level of osteopontin (OPN), a secreted phosphoglycoprotein expressed by a variety of cell types, has been reported as a risk predictor in various cardiovascular diseases.Methods: OPN was determined retrospectively in 150 consecutive patients newly diagnosed with AL amyloidosis. All patients were evaluated according to a routine protocol including electrocardiography, echocardiography and laboratory testing.Results: Mean OPN was 591 ± 37 ng/mL. Cardiac involvement was established in 83 (55.3%). Median OPN plasma level were associated with number of organs involved, renal function, eligibility for high-dose melphalan chemotherapy and autologous stem cell transplantation, and severity of cardiac amyloidosis. Median follow-up was 19.2 months. 1-year all-cause-survival was 83.4%. The cut-offs discriminating 1-year all-cause-mortality for NT-proBNP, troponin T, and OPN were 2544 ng/L, 0.035 µg/L, and 426.8 ng/mL, respectively. Outcome was worse in patients with biomarkers above the individual ROC derived cut-off. A significant improvement of survival was observed in patients with cTNT >0.035 µg/L or NT-proBNP >2544 ng/L and OPN below ROC-derived cut-off of 426.8 ng/mL as compared to patients with OPN above 426.8 ng/L. No further discrimination was achieved by OPN in the cohorts of low troponin T or low NT-proBNP, respectively. Separate multivariate models identified OPN (cut-off 426.8 ng/mL) and troponin T (cut-off 0.035 µg/L) as independent predictors of all-cause-mortality.Conclusions: These data demonstrated that OPN appears to be a valuable marker in the clinical routine for evaluation of patients with AL amyloidosis, especially if it is used in combination with cTNT and/or NT-proBNP.
Gesehen am 23.07.2020